Step 1

Consider the given linear equation,

\(ax+5-3=6x+3-3\)

\(ax+2=6x\)

Step 2

Now, add −ax both side of the equation and solve for x,

\(-ax+ax+2=6x-ax\)

\(6x-ax=2\)

\((6-a)x=2\)

\(x=\frac{2}{6-a}\)

Where \(a\neq 6\) because at \(a = 6\) the value of x is not defined.

Consider the given linear equation,

\(ax+5-3=6x+3-3\)

\(ax+2=6x\)

Step 2

Now, add −ax both side of the equation and solve for x,

\(-ax+ax+2=6x-ax\)

\(6x-ax=2\)

\((6-a)x=2\)

\(x=\frac{2}{6-a}\)

Where \(a\neq 6\) because at \(a = 6\) the value of x is not defined.